2013
DOI: 10.1136/emermed-2012-201465
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the cardiac biomarkers of non-elite athletes completing the 2009 London Marathon

Abstract: We identified runners with troponin levels that, in other circumstances, would raise concern for myocardial necrosis. However absence of adverse clinical sequelae would suggest this rise is physiological. The cause and clinical significance of the increased HSTnT levels seen in those that collapsed is yet to be fully elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
(14 reference statements)
1
27
0
2
Order By: Relevance
“…19,32 However, conflicting data exist regarding the prognostic significance of cardiac biomarkers at exercise, because Baker et al reported higher release among marathon runners who collapsed than among control subjects. 33 To our knowledge, this is the first study in which the presence of EVLF and BNP levels were simultaneously assessed during a climbing expedition, using a handheld echography and a point-of-care capillary assay, allowing immediate results. Previous studies 12,13,15,34 used venous blood samples, which imply more complex logistics and some technical expertise that preclude their use in the hostile environment of HA expeditions.…”
Section: Discussionmentioning
confidence: 99%
“…19,32 However, conflicting data exist regarding the prognostic significance of cardiac biomarkers at exercise, because Baker et al reported higher release among marathon runners who collapsed than among control subjects. 33 To our knowledge, this is the first study in which the presence of EVLF and BNP levels were simultaneously assessed during a climbing expedition, using a handheld echography and a point-of-care capillary assay, allowing immediate results. Previous studies 12,13,15,34 used venous blood samples, which imply more complex logistics and some technical expertise that preclude their use in the hostile environment of HA expeditions.…”
Section: Discussionmentioning
confidence: 99%
“…Acute, prolonged, strenuous‐exercise induced cTn release, including cTn T and I (cTnT and cTnI) has been widely reported in healthy and asymptomatic athletes (Shave et al., ). Both continuous exercise, such as marathon running (Serrano‐Ostáriz et al., ) and cycling (Baker et al., ), and intermittent exercise, such as basketball in adolescents (Nie et al., ), have been shown to trigger the elevation of cTn. With regard to the potential mechanisms, it is assumed that mechanical stretch (George et al., ), myocardial cell ischemia (Hickman et al., ), necrosis (Shave et al., ), or the oxidative stress‐induced increase in membrane permeability (Nie et al., ; Howatson et al., ) may be involved.…”
mentioning
confidence: 99%
“…Four prior studies have investigated cTnT rise in marathon runners utilizing the same high-sensitivity cTnT assay with an average post-marathon value of between 31.1 to 47.0 ng/L. 4,[8][9][10] The median cTnT rise of 45.6 ng/L observed in the CON group is at the higher end of the range seen in prior studies. Peak post-exercise cTnT value is not achieved immediately upon exercise completion with peak post-exercise cTnT and cTnI values reported 1-4 hours following exercise completion.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in agreement with the only other study assessing these populations. 10 Although only a relatively small number of HD runners were recruited, the cohort represented a diverse spectrum of HD pathology. The similarity of the cTnT rise with the CON runners demonstrates that variations in post-marathon cTnT rise cannot be used to reliably identify individuals with undiagnosed cardiac abnormalities.…”
Section: Discussionmentioning
confidence: 99%